A study of mucilage in light microscope photographs acquired by using a different painting material of Gomphonema sp - Alp, M.T.; Sen, B.; Özbay, Ö. (My University, 2011)
This research was based on the patterns of Gomphonema sp. obtained from Lake Hazar (Elazi?, Turkey), which has a high alkali feature. It was carried out by monitoring the live samples of patterns isolated from the littoral part of the lake, which was painted by a different material. It is known, to date, that India ink has been widely used in the painting of live algal sample. In this research, hematoxylen solution, which was commonly used in obtaining images from histologic isolated sample by using light microscope, was used instead of India ink. Incredibly, findings have been spotted in this research, which was carried out for the purpose of photographing the mucilage morphology of Gomphonema sp. in a clearer and more significant sense. Thus, this study was photographed under light microscope that in live isolated samples, dyed by hematoxylen, the cells belonging to Gomphonema sp., which was in the phase of cell division, was completely covered in mucilage and the division was over the mucilage disappearance. The fact that no findings were detected in the literature investigation so far, regarding the taxon belonging to Gomphonemataceae, covered the surrounding mucilage of the cell that completely increased the importance of the data obtained by this research. © 2011 Academic Journals.
Keywords: Diatom; Gomphonema; Lake hazar; Mucilage; Turkey